Development of Zero Energy Evaporative Cooling Storage Structure for Tribal Region of South Gujarat: ZERO ENERGY STORAGE STRUCTURE FOR TRIBAL REGION - Rajesh, R G Burbade; S.N. Singh; S.H. Sengar (Annals of Arid Zone, 2024)
Abstract Zero Energy Evaporative Cooling Storage Structure (ZEECSS) was designed and constructed with two different cooling pads i.e., gunny bags (GB) and small pieces of bricks (SPB) with the capacity of 50 kg to preserve yellowish red fresh tomatoes. In a no-load condition, an average temperature drop of 8±2°C and 9±2°C, with relative humidity varying from 87% to 88%, and cooling efficiency of 84% and 82% respectively was achieved in GB and SPB structure. Under loaded condition (with tomatoes stored in structure) average temperature drop of 10±2°C and 11±2°C, with relative humidity varying from 85% to 87%, and cooling efficiency measuring 88% and 91% was recorded respectively. A qualitative analysis of the stored tomatoes in terms of physiological loss in weight (% PLW), spoilage, shrinkage, total soluble solids (TSS), and pH indicated values of 16.25%, 22.06%, 4.67 cm, 4.34°Brix, and 4.68, respectively, for GB cooling pads, and 14.44%, 20.14%, 4.80 cm, 4.42°Brix, and 4.77, respectively, for SPB cooling pads on 14th day of storage. It was observed that the tomatoes could be stored for 14 days with 20±2% spoilage, compared to ambient conditions where rotting started on or after the 7th to 10th days, with spoilage reaching at 91.36% in next 2-3 days. Cost of structure had been calculated to be Rs. 7115, with 7 months payback period.